Conceptual Approaches to the Formation of Architecture of Documents of Strategic Planning in Russia - O. O. Smirnova; L. K. Bocharova; L. A. Belyaevskaya-Plotnik; Ju. N. Bogdanova (Модернизация, инновация, развитие, 2019)
Purpose: of the article is to prepare evidence-based proposals for the formation of document architecture, strategic planning, fundamental for modern needs and ensuring the integrity of the strategy for all levels of government and business, as well as to ensure the implementation of the principles of unity, integrity, continuity, continuity and delineation of powers in organizing and system functioning, strategic planning as part of a single management cycle. In the framework of the task of creating the architecture of documents, strategic planning also solves the important task of linking issues of socioeconomic development and ensuring national security, and as a result – improving the efficiency of public administration, ensuring coherence and coordination of the country's strategic priorities. Methods: the main method of work is the disclosure of the principles of strategic planning. The architecture of strategic planning documents under development is based on the disclosure of regulatory acts of the Federal Law dated 28.06.2014 N 172-FZ “On Strategic Planning in the Russian Federation”. Results: the absence of normatively fixed principles and a system for ensuring strategic planning, as well as the procedure for implementing strategic planning, leads to inconsistency of the approved strategies and forecasting, the development of new documents and studies in the Federal Law “On Strategic Planning in the Russian Federation” and other violations of the systematic approach. In this regard, it is necessary to determine the architecture of the system of strategic planning documents developed as part of the target definition, forecasting, planning and programming.Conclusions and Relevance: the architecture of strategic planning documents proposed in the article is based on the creation of a three-level document system with a central place in it the National Security Strategy of the Russian Federation as the main document of strategic goalsetting. In accordance with Federal Law N 172-FZ, the level of forecasting, target definition, planning and programming allows you to add a conceptual level that ensures the quality of the overall ideological superstructure, which should provide an idea of what kind of character for the state and its position in the world the strategic planning system should provide. Taking into account the task of minimizing amendments and clarifications to the Federal Law “On Strategic Planning in the Russian Federation”, the proposed changes are more in the nature of clarifying the provisions of this law. The architecture of the documents built in this way will allow implementing and, if necessary, further detailing the principles of strategic planning defined by law 172-FZ and, above all, the principles of continuity, balance of the strategic planning system.